The influence of teacher support on vocational college students’ information literacy: The mediating role of network perceived usefulness and information and communication technology self-efficacy - Chen, Qiaoyun; Ma, Ying (Frontiers in Psychology, 2022)
This paper uses the network perceived usefulness scale, ICT self-efficacy scale, teacher support questionnaire and higher vocational students' information literacy scale to explore the multiple intermediary functions of network perceived usefulness and ICT self-efficacy in teacher support and higher vocational students' information literacy from the perspective of multiple intermediary effects, and uses structural equation model for data modeling and analysis. The results show that the information literacy of higher vocational students is positively correlated with teacher support, usefulness of network perception and ICT self-efficacy. Teachers' support is positively correlated with ICT self-efficacy and network perceived usefulness, and network perceived usefulness and ICT self-efficacy play a significant mediating role between teachers' support and information literacy of higher vocational students. Based on the research results, some suggestions are put forward to guide teachers to help students clearly recognize the role of information technology, improve ICT self-efficacy, improve information literacy and better integrate into digital society.